Aesthetic Alternative Using Composite Resin to Replace a Missing Tooth. A Case Report - Yuritza Hernández Núñez; Dileydi Ramos Rodríguez; Anamary Enríquez León (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Patients who experience dental trauma resulting in permanent tooth loss are often prosthetically rehabilitated through any of its variants. However, it is uncommon to rehabilitate a patient using composite resin when a tooth is lost. The case of a patient who had lost a maxillary central incisor years ago and its space had been occupied by the lateral incisor is presented. The missing tooth was built up through the enlargement of the lateral incisor using the layering technique or stratification with Brilliant New Line resin. This paper aims at demonstrating a more economical and simpler alternative for restoring the aesthetics of a patient with unfavorable prognosis.